Modelling and Stability Analysis of Brushless Doubly Fed Generators - Abderahmane Ganouche; Hacene Bouzekri; Antar Beddar (Universitas Ahmad Dahlan, 2017)
The brushless doubly-fed machine (BDFM) continues to attract increasing interest for applications in wind generation where, robustness and low servicing costs are its principles advantages. The construction aspect of the BDFM has been widely studied and currently this machine can be build with good performances. However, the control aspect remains difficult to achieve and some studies show that the BDFM is less stable than the doubly-fed induction machine. To explore the BDFM stability in all operating mode, this paper proposes a stability analysis of a grid-connected variable speed wind turbine-based BDFM. For this purpose, a linearized small signals mathematical model is proposed which takes into account both grid and control disturbances. Then, the effect of electrical parameters variation and operating speed change on the stability of the BDFM has been studied. The stability has been investigated through simulation implementation. The obtained results demonstrate the validity and the superiority of the proposed model.